Evidence from measuring community flood resilience in Asia. - Laurien, Finn (Asian Development Bank, 2019)
Measuring community disaster resilience helps communities and organizations understand the disaster development system driving their risk and well being outcomes. This paper finds that long term and transformative approaches and systemic interventions involving multiple stakeholders are most likely to succeed and have cobenefits for community development.